Cognitive-behavioural therapy compared with standardised medical care for adults with dissociative non-epileptic seizures: the CODES RCT. - Goldstein, Laura H (Health Technol Assess, 2021)
BACKGROUND: Dissociative (non-epileptic) seizures are potentially treatable by psychotherapeutic interventions; however, the evidence for this is limited. OBJECTIVES: To evaluate the clinical effectiveness and cost-effectiveness of dissociative seizure-specific cognitive-behavioural therapy for adults with dissociative seizures. DESIGN: This was a pragmatic, multicentre, parallel-arm, mixed-methods randomised controlled trial. SETTING: This took place in 27 UK-based neurology/epilepsy services, 17 liaison psychiatry/neuropsychiatry services and 18 cognitive-behavioural therapy services. PARTICIPANTS: Adults with dissociative seizures in the previous 8 weeks and no epileptic seizures in the previous year and meeting other eligibility criteria were recruited to a screening phase from neurology/epilepsy services between October 2014 and February 2017. After psychiatric assessment around 3 months later, eligible and interested participants were randomised between January 2015 and May 2017. INTERVENTIONS: Standardised medical care consisted of input from neurologists and psychiatrists who were given guidance regarding diagnosis delivery and management; they provided patients with information booklets. The intervention consisted of 12 dissociative seizure-specific cognitive-behavioural therapy 1-hour sessions (plus one booster session) that were delivered by trained therapists, in addition to standardised medical care. MAIN OUTCOME MEASURES: The primary outcome was monthly seizure frequency at 12 months post randomisation. The secondary outcomes were aspects of seizure occurrence, quality of life, mood, anxiety, distress, symptoms, psychosocial functioning, clinical global change, satisfaction with treatment, quality-adjusted life-years, costs and cost-effectiveness. RESULTS: In total, 698 patients were screened and 368 were randomised (standardised medical care alone, n = 182; and cognitive-behavioural therapy plus standardised medical care, n = 186). Primary outcome data were obtained for 85% of participants. An intention-to-treat analysis with multivariate imputation by chained equations revealed no significant between-group difference in dissociative seizure frequency at 12 months [standardised medical care: median of seven dissociative seizures (interquartile range 1-35 dissociative seizures); cognitive-behavioural therapy and standardised medical care: median of four dissociative seizures (interquartile range 0-20 dissociative seizures); incidence rate ratio 0.78, 95% confidence interval 0.56 to 1.09; p = 0.144]. Of the 16 secondary outcomes analysed, nine were significantly better in the arm receiving cognitive-behavioural therapy at a p-value < 0.05, including the following at a p-value ≤ 0.001: the longest dissociative seizure-free period in months 7-12 inclusive post randomisation (incidence rate ratio 1.64, 95% confidence interval 1.22 to 2.20; p = 0.001); better psychosocial functioning (Work and Social Adjustment Scale, standardised treatment effect -0.39, 95% confidence interval -0.61 to -0.18; p < 0.001); greater self-rated and clinician-rated clinical improvement (self-rated: standardised treatment effect 0.39, 95% confidence interval 0.16 to 0.62; p = 0.001; clinician rated: standardised treatment effect 0.37, 95% confidence interval 0.17 to 0.57; p < 0.001); and satisfaction with treatment (standardised treatment effect 0.50, 95% confidence interval 0.27 to 0.73; p < 0.001). Rates of adverse events were similar across arms. Cognitive-behavioural therapy plus standardised medical care produced 0.0152 more quality-adjusted life-years (95% confidence interval -0.0106 to 0.0392 quality-adjusted life-years) than standardised medical care alone. The incremental cost-effectiveness ratio (cost per quality-adjusted life-year) for cognitive-behavioural therapy plus standardised medical care versus standardised medical care alone based on the EuroQol-5 Dimensions, five-level version, and imputed data was £120,658. In sensitivity analyses, incremental cost-effectiveness ratios ranged between £85,724 and £206,067. Qualitative and quantitative process evaluations highlighted useful study components, the importance of clinical experience in treating patients with dissociative seizures and potential benefits of our multidisciplinary care pathway. LIMITATIONS: Unlike outcome assessors, participants and clinicians were not blinded to the interventions. CONCLUSIONS: There was no significant additional benefit of dissociative seizure-specific cognitive-behavioural therapy in reducing dissociative seizure frequency, and cost-effectiveness over standardised medical care was low. However, this large, adequately powered, multicentre randomised controlled trial highlights benefits of adjunctive dissociative seizure-specific cognitive-behavioural therapy for several clinical outcomes, with no evidence of greater harm from dissociative seizure-specific cognitive-behavioural therapy. FUTURE WORK: Examination of moderators and mediators of outcome. TRIAL REGISTRATION: Current Controlled Trials ISRCTN05681227 and ClinicalTrials.gov NCT02325544. FUNDING: This project was funded by the National Institute for Health Research (NIHR) Health Technology Assessment programme and will be published in full in Health Technology Assessment; Vol. 25, No. 43. See the NIHR Journals Library website for further project information.